Pengaruh Pemberian Tindakan Pijat Oksitosin Terhadap Keberhasilan Proses Menyusui Pada Ibu Nifas - Desy Syswianti; Tri Wahyuni; Dina Mardiana (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
Background: Eighty percent of maternal breastfeeding at Dina Clinik not successful during the process of breastfeedingthat resulted in the low (55%-60%) coverage of exclusive breastfeeding. Giving massage oxytosin can increase success ofthe process of breastfeeding because psychologically enhance attachment and bounding and physiological hormoneoxytosin increase releasing`.Research method: Pre-Experiment with the static group comparison design. Research location taken at Dina MardianaClinik. Subject of research are postpartum mothers and newborns treated at Dina Clinik. Two hours postpartum motherchildbed was given massage oxytosin by a husband with cheklist guidelines on the treatment group. The success ofbreastfeeding observed on the control and treatment groups with observation instrument MBA Tool.Results: Giving massage oxytosin in the treatment group increased breastfeeding success with an average of 6800. Thereare massage oxytosin effect to the success of breastfeeding on maternal childbed at Dina Clinik in 2017 with a significantof p = .004.Conclusion: This Study concludes that there are effect of the influence of massage oxytosin against to success of theprocess of breastfeeding on maternal childbed.Keywords: Oxitosin Massage, Success of Breastfeeding process, Postpartum Mother